Nxf7 deficiency impairs social exploration and spatio-cognitive abilities as well as hippocampal synaptic plasticity in mice - Callaerts-Vegh, Zsuzsanna; Ahmed, Tariq; Vermaercke, Ben; Marynen, Peter; Balschun, Detlef; Froyen, Guy; D’Hooge, Rudi (Frontiers in Behavioral Neuroscience, 2015)
Nuclear RNA export factors (NXF) are conserved in all metazoans and are deemed essential for shuttling RNA across the nuclear envelope and other post-transcriptional processes (such as mRNA metabolism, storage and stability). Disruption of human NXF5 has been implicated in intellectual and psychosocial disabilities. In the present report, we use recently described Nxf7 knockout mice as an experimental model to analyze in detail the behavioral consequences of clinical NXF5 deficiency. We examined male Nxf7 knockout mice using an extended cognitive and behavioral test battery, and recorded extracellular field potentials in the hippocampal CA1 region. We observed various cognitive and behavioral changes including alterations in social exploration, impaired spatial learning and spatio-cognitive abilities. We also defined a new experimental paradigm to discriminate search strategies in Morris water maze and showed significant differences between Nxf7 knockout and control animals. Furthermore, while we observed no difference in nose poke suppression in an conditioned emotional response protocol, Nxf7 knockout mice were impaired in discriminating between differentially reinforced cues in an auditory fear conditioning protocol. This distinct neurocognitive phenotype was accompanied by impaired hippocampal long-term potentiation, while long-term depression was not affected by Nxf7 deficiency. Our data demonstrate that disruption of murine Nxf7 leads to behavioral phenotypes that may relate to the intellectual and social deficits in patients with NXF5 deficiency.